2014
DOI: 10.1111/febs.12746
|View full text |Cite
|
Sign up to set email alerts
|

Homooligomerization is needed for stability: a molecular modelling and solution study of Escherichia coli purine nucleoside phosphorylase

Abstract: Although many enzymes are homooligomers composed of tightly bound subunits, it is often the case that smaller assemblies of such subunits, or even individual monomers, seem to have all the structural features necessary to independently conduct catalysis. In this study, we investigated the reasons justifying the necessity for the hexameric form of Escherichia coli purine nucleoside phosphorylase -a homohexamer composed of three linked dimers -since it appears that the dimer is the smallest unit capable of catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Negative, doubly charged phosphate anion rearranges, upon binding, Hbonds, and attracts positively charged residues affecting dynamics of protein backbone. In this context, the use of Arg24Ala mutant in this work confirmed previous knowledge [19][20][21][22][23][24] on the key role of Arg24 in the PNP catalysis.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Negative, doubly charged phosphate anion rearranges, upon binding, Hbonds, and attracts positively charged residues affecting dynamics of protein backbone. In this context, the use of Arg24Ala mutant in this work confirmed previous knowledge [19][20][21][22][23][24] on the key role of Arg24 in the PNP catalysis.…”
Section: Resultssupporting
confidence: 89%
“…This remarkable enzyme has been the subject of our scientific interest for many years [19][20][21][22][23][24]. PNPs are versatile catalysts of the reversible phosphorolysis of purine (2′-deoxy)-ribonucleosides [25,26]: purine (2′-deoxy)-ribonucleoside + orthophosphate ↔ purine base + (2′-deoxy)-ribose 1-phosphate Due to their catalytic function and much broader specificity compared with their trimeric human counterpart [26], hexameric PNPs (e.g., from E. coli) have been investigated for the efficient synthesis of nucleoside analogues [27] as well as for the activation of pro-drugs in anti-cancer gene therapies [28].…”
mentioning
confidence: 99%
“…Noteworthy, the enzymatic activity of E. coli PNP that is a trimer of dimers was recently investigated in detail and it was convincingly proven that only the hexameric structure displays activity. [23] It was found that Urd and 6C2FP in concentrations up to 80 mM and 55 mM, respectively, do not inhibit the immobilised enzymes.…”
Section: Introductionmentioning
confidence: 94%
“…Immobilisation also allows for a convenient and easier recovery of the biocatalysts and simplifies the design of a reactor. [22] Considering the multimeric nature of the enzyme, [23] and some examples where NPs were successfully immobilised on a hydrophilic support (e.g., epoxide), [24] we chose MagReSyn microspheres as an immobilisation carrier. These microspheres are made of magnetite particles combined with a hydrophilic polymer with epoxide-functional groups, [25] [a] Solubility was measured by UV spectroscopy at the maximum wavelength of each compounds (284-288 nm) in 2 mM potassium phosphate buffer (pH 7.0).…”
Section: Introductionmentioning
confidence: 99%
“…For many years we have been studying a homohexameric enzyme purine nucleoside phosphorylase (PNP, purine nucleoside orthophosphate ribosyl transferase, http://www.chem.qmul.ac.uk/iubmb/enzyme/EC2.4.2.1.html) and the conformational changes of its six active sites upon ligand binding, with the final goal of understanding the highly complex mechanism of this enzyme action . PNP catalyses the reversible phosphorolytic cleavage of the glycosidic bond of purine ribo‐ and deoxyribonucleosides:(deoxy)purine nucleoside+orthophosphate=purine base+(2‐deoxy)ribose‐1‐phosphate.…”
Section: Introductionmentioning
confidence: 99%